Optimally solving banks' legacy problems - Anatoli Segura; Javier Suárez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
We characterize policy interventions directed to minimize the cost to the deposit guarantee scheme and the taxpayers of banks with legacy problems. Non-performing loans (NPLs) with low and risky returns create a debt overhang that induces bank owners to forego profitable lending opportunities. NPL disposal requirements can restore the incentives to undertake new lending but, as they force bank owners to absorb losses, can also make them prefer the bank being resolved. For severe legacy problems, combining NPL disposal requirements with positive transfers is optimal and involves no confl ict between minimizing the cost to the authority and maximizing overall surplus.
Keywords: G01; G20; G28; 330; non performing loans; deposit insurance; debt overhang; optimal intervention; state aid